2014
DOI: 10.1080/07399332.2014.948626
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intimate Partner Violence Among Women Visiting Health Care Centers in Palestine Refugee Camps in Jordan

Abstract: This study was conducted to investigate the prevalence of intimate partner violence (IPV) among a sample of women visiting health care centers in Palestine refugee camps in Jordan. We found that different types of IPV, including physical, emotional, sexual, economic, and control behaviors by the partners were experienced by the participants. This study was among a number of studies that investigated this phenomenon in residents of Palestinian camps. It adds to existing studies in this field, however, as it foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 16 publications
0
37
1
3
Order By: Relevance
“…Our findings indicated a low incidence of IPV among the refugee women, which stands in contrast to the literature demonstrating a high prevalence of IPV among refugee women and among Hispanic women in general [3, 47, 50]. Generally, women who are in violent relationships with a partner are frequently more vulnerable and unable to sustain day-to-day activities, reducing their perceptions of self-efficacy [16, 51, 52].…”
Section: Discussioncontrasting
confidence: 84%
“…Our findings indicated a low incidence of IPV among the refugee women, which stands in contrast to the literature demonstrating a high prevalence of IPV among refugee women and among Hispanic women in general [3, 47, 50]. Generally, women who are in violent relationships with a partner are frequently more vulnerable and unable to sustain day-to-day activities, reducing their perceptions of self-efficacy [16, 51, 52].…”
Section: Discussioncontrasting
confidence: 84%
“…Moreover, health and social inequalities for refugees across the EMR result in deprivation-related multi-morbidity including mental illness [52]. Intimate partner violence is also prevalent across much of the EMR [53]. …”
Section: Discussionmentioning
confidence: 99%
“…Living conditions of women in refugee camps could add to the significance of the study. Refugee camps are characterized by poor socio-economic living standards of its dwellers, relatively low educational achievements, crowdedness, and, consequently, having dwellers prone to altered health status (Al-Modallal 2012b; Al-Modallal et al 2015). These factors are expected to trigger women's exposure to IPV and inversely impact their physical health.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…In their study of employed women, Al-Modallal and colleagues indicated that nearly half of the respondents reported IPV victimization (Al-Modallal et al 2012). Beyond that, several other studies focusing on identifying prevalence rates of IPV by type were found (Al-Modallal et al 2015;Al-Nsour et al 2009;Clark et al 2009). These studies agreed on the fact that IPV is a prevailed problem faced by Jordanian women.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation